Contraction and pore pressure behavior of a silty sand deposit subjected to an extended shaking history. Issue 114 (November 2018) - El-Sekelly, W.; Mercado, V.; Abdoun, T.; Dobry, R.; Sepulveda, A.
Abstract: The paper presents the implementation of an identification technique to characterize the pore pressure behavior of a silty sand centrifuge deposit subjected to more than 70 seismic shakings with full pore pressure dissipation between shakings. The seismic shakings were meant to crudely simulate the seismic history of field deposits in some very seismically active zones in California. The technique estimates shear stresses and strains based on acceleration and pore pressure recorded using a vertical array of sensors in the deposit. A constitutive model was implemented to identify optimal material parameters controlling the contractive behavior of the soil based on the recorded response of all shakings. It was found that the seismic history of soil deposits plays an important role in determining the contractive tendency of the material, significantly influencing the pore pressure response of the deposit. That is, the seismic history can reduce or increase the resistance of a deposit to contraction and liquefaction. Highlights: A constitutive model was implemented to identify optimal material parameters controlling the contractive behavior of the soil. A centrifuge deposit was subjected to more than 70 seismic shakings with full pore pressure dissipation between shakings. The seismic history of soil deposits plays an important role in determining the contractive tendency of the material. The seismic history can reduce or increase the resistance of a deposit to contraction and liquefaction.